Impact of the COVID-19 pandemic on the incidence of healthcare facility-onset Clostridioides difficile infection in hospitalized patients with sepsis: Interrupted time series analysis using Japanese Diagnosis Procedure Combination data. (February 2023) - Endo, Koji; Mizuno, Kayoko; Takeuchi, Masato; Kawakami, Koji
Abstract: Objectives: Healthcare facility-onset Clostridioides difficile infection (HO-CDI) is a major nosocomial infection associated with high mortality and healthcare costs. We aimed to determine if HO-CDI incidence decreased due to the COVID-19 pandemic. We hypothesized that the pandemic decreased HO-CDI as healthcare workers became more diligent in handwashing and sanitization. Methods: In this retrospective cohort study, adult patients with sepsis hospitalized in general wards from January 2018 to February 2021 were identified using a nationwide Japanese administrative database. Patients were divided into two groups according to the hospitalization date (before and after the first declaration of a state of emergency). The primary outcome was a change in the level of the HO-CDI monthly incidence ratio (per 10000 patient-days). Results: Of the 49, 156 eligible hospitalizations for sepsis, 41, 870 were before and 7, 283 were after the first state of emergency declaration. Interrupted time-series (ITS) analysis showed no significant difference in the HO-CDI incidence ratio after Japan's first state of emergency declaration (level change −1.0, 95% confidence interval (CI) −8.6 to 6.6, p = 0.8, slope change 0.06, 95% CI -0.17 to 0.3, p = 0.6). The overall HO-CDI incidence ratio was 3.86/10000 patient-days (interquartile range 2.97–4.53); higher incidence existed in subgroups with older adults or a lower Barthel index at admission. Conclusions: No significant change in HO-CDI incidence was observed in patients with sepsis hospitalized in general wards before and after Japan's first state of emergency declaration. Our study revealed that HO-CDI in general wards in Japan had been consistently decreasing since before the COVID-19 pandemic. Highlights: HO-CDI occurred in approximately 2% of patients with sepsis in the general wards. There was no impact of the COVID-19 pandemic on the incidence ratio of HO-CDI. The incidence ratio of HO-CDI had been decreasing even before the pandemic.